2015
DOI: 10.1002/ejoc.201500873
|View full text |Cite
|
Sign up to set email alerts
|

Calix[6]arene Functionalized at Four Bridges: Conformation and Intramolecular Guest Exchange

Abstract: Reaction of the tert‐butoxycarbonyl derivative of p‐tert‐butylcalix[6]arene (2) with excess NBS under irradiation yields a calixarene with four bromomethine bridges as the major product (3). On the basis of the number of signals in the NMR spectrum, to the product was assigned a 1,2,4,5‐substitution pattern. X‐ray crystallography indicates that the product possesses the rct2 configuration and crystallized as a mixture of two conformers. The major form in the crystal exists in a 1,2,3‐alternate conformation whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…On this basis, the dynamic process is assigned to a topomerization process involving Ar−OMe rotations (Figure ), in which the “in” and “out” OMe groups on opposite rings are exchanged, and more generally, between pairs of t Bu, aromatic, and methoxy protons on opposite rings (i.e., in a “1,4” relationship). A similar dynamic process was previously observed for the tetrabromo tert ‐butoxycarbonyl derivative of p‐tert ‐butylcalix[6]arene 19 a …”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…On this basis, the dynamic process is assigned to a topomerization process involving Ar−OMe rotations (Figure ), in which the “in” and “out” OMe groups on opposite rings are exchanged, and more generally, between pairs of t Bu, aromatic, and methoxy protons on opposite rings (i.e., in a “1,4” relationship). A similar dynamic process was previously observed for the tetrabromo tert ‐butoxycarbonyl derivative of p‐tert ‐butylcalix[6]arene 19 a …”
Section: Resultssupporting
confidence: 77%
“…A similard ynamic process was previously observed fort he tetrabromo tert-butoxycarbonyl derivativeo fp-tert-butylcalix [6]arene 19 a. [25] From the chemical shift difference between pairs of axial and equatorial protons at 193 Ka nd their coalescence temperature (208 K), ab arriero f9 .9 kcal mol À1 was calculated for the ArÀOMe rotation process. [26] This barrier is substantially lower than that determinedf or the rotation of the OBoc groups of 19 a (18.4 kcal mol À1 ).…”
Section: Low-temperature 1 Hn Mr Spectra and Rotational Barrierssupporting
confidence: 59%
“…Initially, derivatives 5b / 6b and 5c / 6c were synthesized following the procedure reported by Singh and coworkers. , In detail, p - tert -butylcalix­[6]­arene hexamethyl ether 1a was first treated with n -BuLi/TMEDA, and the anion was then reacted with the corresponding alkyl halide electrophile, leading to derivatives 5 and 6 fixed in the cone or 1,2,3-alternate conformation, respectively (Scheme ). Successively, derivatives 5b / 6b and 5c / 6c were characterized by 1D and 2D NMR in accordance with the considerations reported in the literature. , The cone and 1,2,3-alternate structural assignment was confirmed by solid-state X-ray structures of derivatives 6c and 5c (Figure ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The pseudorotaxane initially formed (the kinetic product) shows the calix wheel in the 1,2,3-alternate conformation and is conformationally less stable; therefore, it interconverts to a new one (the thermodynamic product) in which the calix wheel adopts a cone conformation . Very recently, it was found that the introduction of alkyl groups at the methylene bridges of the calix[6]­arene macrocycle leads to new derivatives (e.g., 5a and 6a ), which show a high degree of conformational stability. Thus, derivatives fixed in the 1,2,3-alternate conformation (e.g., 6a ) have been isolated and characterized both in solution, by one-dimensional (1D) and two-dimensional (2D) nuclear magnetic resonance (NMR) studies, and in the solid state, by X-ray diffractometry .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a calix[6]arene derivative with a pair of opposite chloromethylene bridges was prepared via a lithiation/oxygenation of 1c , affording a derivative with a pair of opposite bridges hydroxylated, followed by reaction of the product with SOCl 2 /Et 3 N . Bromination of the methylene bridges of a Boc‐protected calix[6]arene derivative with excess NBS proceeded only up to the tetrabrominated stage …”
Section: Introductionmentioning
confidence: 99%